Positive youth development-based physical activity to enhance social awareness in middle school students - Varhatun Fauziah; Nuridin Widya Pranoto; Tjung Hauw Sin; Ahmad Chaeroni (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
Physical education has the potential to support not only students’ physical development but also their social and emotional growth. However, physical activity in many physical education classes is still implemented without a clear pedagogical design aimed at developing students’ social awareness. This study examined the effect of Positive Youth Development (PYD)-based physical activity on strengthening social awareness among middle school students. A quasi-experimental pretest–posttest control group design was used involving 60 students (aged 13–15 years) who were divided into an experimental group (n = 30) and a control group (n = 30). The experimental group participated in physical education activities designed using PYD principles such as cooperation, empathy, responsibility, and positive social interaction, while the control group followed conventional physical education learning. Social awareness (caring) was measured using adapted items from the Chinese Positive Youth Development Scale covering empathy, prosocial behavior, social relations, and emotional regulation. The results showed a significant increase in social awareness in the experimental group compared with the control group (p < 0.05), indicating that PYD-based physical activity can support the development of students’ social competence in physical education learning.